The dynamics of student engagement through the lens of involvement and self-determination theories - Chin, Wei Mun; Ahmad, Nor Aniza; Ismail, Ismi Arif; Alias, Siti Noormi (Human Resources Management Academic Research Society (HRMARS), 2024)
A comprehensive review of the literature reveals significant theoretical gaps in understanding student engagement such as cultural differences and the challenges posed by the growing prevalence of online and blended learning environments. There is a need for better approaches to explore the multifaceted nature of student engagement to inform effective educational practices and foster a supportive learning environment. This paper examines the conceptualization and theoretical frameworks surrounding student engagement by focusing on Theory of Involvement and The Self-Determination Theory. This paper argues for the integration of these theories to provide a more comprehensive understanding of student engagement and the need for future research to consider diverse theoretical perspectives as well as the dynamic nature of student engagement across various settings.